Kepatuhan Pemeriksaan PPIA (Pencegahan Penularan HIV dari Ibu Ke Anak) Ibu Hamil dengan Risiko HIV (Human Immunodeficiency Virus) - Anang Wibowo; Djoko Priyatno (Poltekkes Kemenkes Semarang, 2019)
Human Immunodeficiency Virus (HIV) is an infectious disease with a death rate and the number of disease incidence is high and requires the diagnosis and the therapy long enough. The success of the program depends on the PPIA socialization of HIV and Syphilis in pregnant women, as well as compliance checked her pregnancy during pregnancy for early detection of HIV and Syphilis that is useful for the treatment of early and proper while the results the examination showed reactive. The purpose of this research to know description of compliance inspection of PPIA (prevention of HIV transmission from mother to child) of pregnant women with HIV risk in public health II in Baturraden. The method is observational approach time crosssectional tests. Population in the study are all pregnant women and pregnant women throughout the research sample of trimester I, timester II, and trimester III who programme PPIA in public health II in Baturraden of this year in 2018 as many as 100 people. The research results obtained compliance examination of the PPIA pregnant women HIV risk i.e. age 35-44 in 76%; secondary education diploma 100%; and employment status of civil servant or the student as much as 100%. While 55% of disobedience at 15-24 years old; elementary school level 73%; and a housewife 59%. The higher the education, age, and occupation of a person then the PPIA program to carry out compliance higher.